Electrical and raman scattering studies of ZnO:P and ZnO:Sb thin films - Campos, J. Ayres de (2010)
A study on the structure, electrical and optical properties of ZnO thin films produced by r.f. magnetron sputtering and implanted either with phosphorous (P) or antimony (Sb) is reported in this work. Raman spectroscopy, X-ray diffraction, optical transmittance and Hall effect measurements have been employed to characterize the samples. X-ray diffraction and Raman scattering patterns confirm that, after a 500ºC annealing, the doped films keep a polycrystalline nature with (002) preferred orientation. These films are very transparent and Hall effect results show that all have p-type conduction, despite doping ion and dose. The electric resistivity reaches values of 0.012 (cm) and 0.042 (cm) for the P and Sb-doped samples, respectively